Description of male, larva and pupa of Stibasoma theotaenia (Wiedemann) (Diptera-Tabanidae) - Coscarón, Sixto (1999)
Unknown male, larva and pupa of Stibasoma theotaenia from northern Argentina are described and illustrated. Larvae were collected from terrestrial Bromeliaceae of Aechnea sp. and maintained in the laboratory through development.